Yoga's Reintroduction to Modern China via the West - Zhang, Minyu (Significant Others, Significant Encounters: Essays on South Asian History and Literature, 2023)
As the Buddhist community in China carried forth the Buddhist yogic traditions into the modern era, a new form of yoga was imported to China via the West as the intermediary in a global network of knowledge transmission with metropolitan port cities like Shanghai as its enclaves. By examining newspapers, archives, and books published in the first half of the twentieth century, this chapter recollects the largely forgotten early history of yoga in modern China. Buddhist scholar Liu Renhang, with his translation of Japanese scholar Kaiten Nukariya’s study of yoga in North America, was the first to introduce yoga as a remedy for the nation, then suffering from endless warfare. The theosophist Hari Prasad Shastri lectured on yoga and established a yoga study group called “Holy Yoga”. The first teacher to offer yoga classes regularly in China was Eugenia Peterson, later known as Indra Devi, and her assistant Michael Volin. They successfully enlisted hundreds of pupils, many of whom were Westerners living in Shanghai. However, with the demise of the Shanghai concessions, the spread of yoga in modern China halted abruptly before it was incorporated into the everyday life of ordinary Chinese people.